A supporting procedure for creating dynamically generated reports - Đạo, Đặng Hữu; Nghị, Lê Hữu; Tuấn, Nguyễn Minh; Tùng, Hoàng Đỗ Thanh (Journal of Computer Science and Cybernetics, 2012)
See full text.